Model Keuangan Mikro Digital Berbasis Green Economy Sebagai Sumber Permodalan UMKM Perempuan di Kabupaten Serdang Bedagai - Suwadi; Yenni Arfah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to develop a conceptual model for green economy-based digital microfinance as an effort to improve financial literacy, strengthen managerial capacity, and promote the sustainability of women's MSMEs. The method used was Research and Development (R&D), with a modification of the Borg and Gall model, divided into four stages: preliminary study and needs analysis, model development, limited trials and evaluation, and model finalization. The research was conducted in a participatory manner involving the local community in Serdang Bedagai Regency. The results showed that the developed model was able to improve financial literacy skills, with an average increase of 22% in the understanding of transaction recording and a 30% increase in the ability to prepare simple cash flow statements. The integration of green economy principles encouraged 65% of MSMEs to begin implementing simple efficiency and waste management strategies, while the use of mobile learning was appreciated by 91% of respondents for providing flexible learning access. The implications of this research are the creation of an innovative conceptual framework that not only strengthens financial literacy but also links environmentally friendly practices with the microfinance system, while utilizing digital technology to empower women's MSMEs in rural areas.